1990
DOI: 10.1007/bf01402185
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous interbody osteosynthesis in the treatment of thoracolumbar traumatic or tumoural lesions

Abstract: The authors describe a technique of percutaneous interbody osteosynthesis applicable to the dorsal and lumbar spine. 51 patients were so treated for different aetiologies: traumatic conditions (35 cases) and tumoural lesions (16 cases). The material used consisted of special instruments that are positioned in double obliquity by a percutaneous posterolateral approach. A posterior approach limited to the pathological focus was used jointly whenever a graft or a decompression was necessary (19 cases). Several ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…With the birth of Percutaneous instrument in the 1990s, it was easy to see that the stabilization of Percutaneous led to important benefits for patients from the advantages of new technique [7]. In 2008, Pelegri et al [8] reported spinal Percutaneous stabilization of the lumbar and thoracolumbar spine fractures without neurological deficit.…”
Section: Introductionmentioning
confidence: 98%
“…With the birth of Percutaneous instrument in the 1990s, it was easy to see that the stabilization of Percutaneous led to important benefits for patients from the advantages of new technique [7]. In 2008, Pelegri et al [8] reported spinal Percutaneous stabilization of the lumbar and thoracolumbar spine fractures without neurological deficit.…”
Section: Introductionmentioning
confidence: 98%